Biodegradation Kinetics of Phenol, 2,4,6-Trichlorophenol and Pentachlorophenol with ligninolytic enzymes from Dichomitus Squalens - Zupan, Nastja; Babic, Janja; Pavko, Aleksander (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Biodegradation of phenol, 2,4,6-trichlorophenol and pentachlorophenol was investigated using Dichomitus squalens cultivation media filtrates with initial laccase and manganese peroxidase activities of 1000 U L-1 and 300 U L-1, respectively. Decomposition of all three biocides was studied at T = 28 Â°C, pH = 4.5 and initial concentrations around 6 mg L-1 and the kinetics evaluated on the basis of the time course of the biocide concentration data. Integral analysis revealed 1st order reaction for all three pollutants and the corresponding reaction rate constants and initial concentrations for phenol, 2,4,6-TCP and PCP were estimated from linearized experimental data. The rate equations obtained allow estimation of the times necessary for a particular biocide conversion. The toxicity of reactants and products to the bacterium Vibrio fischeri before and after 48-hours degradation showed that the products were less toxic than the reactants in all three cases. The initial solutions of the three toxic substances caused 54 - 62 % inhibition of the bacterium Vibrio fischeri, while after 48 hours of degradation, 57 % reduction in the toxicity of phenol, 50 % reduction of 2,4,6-TCP and 29 % reduction of PCP was achieved.Â 